PENGARUH LATAR BELAKANG PENDIDIKAN, UKURAN USAHA DAN LAMANYA USAHA TERHADAP KUALITAS LAPORAN KEUANGAN UMKM AGRIBISNIS DI KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Metaness, Putri; Pebriani, Reny Aziatul; M. Nurkholis (STIE Mahardhika, 2024)
This study aims to analyze the influence of educational background, business size, and business duration on the quality of financial statements in Agribusiness SMEs in Talang Kelapa District. Financial statements serve as a crucial tool for various users to make informed economic decisions, providing insights into financial performance and cash flows. The research adopts a quantitative approach, with data gathered through questionnaires and interviews. A total of 80 responses were collected using purposive sampling techniques. The analysis reveals that, individually, educational background, business size, and business duration have a positive and significant impact on the quality of financial statements (sig < alpha = 0.05). Additionally, the independent variables collectively show a positive influence on the financial statement quality of Agribusiness SMEs (sig < alpha = 0.05), indicating that these factors are essential for improving the reliability and accuracy of financial reporting in this sector.